Fluoxetine reverses behavior changes in socially isolated rats: role of the hippocampal GSH-dependent defense system and proinflammatory cytokines - Peric, Ivana; Gass, Peter (European archives of psychiatry and clinical neuroscience, 2017)
Exposure of an organism to chronic social isolation (CSIS) has been shown to have an important role in depression. Fluoxetine (Flx) is a first-line treatment for depression; however, its downstream mechanisms of action beyond serotonergic signaling remain ill-defined. We investigated the effect of 3 weeks of Flx (15 mg/kg/day) treatment on behavioral changes and protein expression/activity of the GSH-dependent defense system, including reduced glutathione (GSH), glutathione peroxidase (GPx), glutathione reductase (GLR), and glutathione S-transferase (GST), as well as catalase (CAT), in the hippocampus of rats exposed to 6 weeks of CSIS. The subcellular distributions of nuclear factor-κB (NF-κB), as well as, cytosolic IL-1β and IL-6 protein expression, were also determined. CSIS induced depressive- and anxiety-like behaviors, evidenced by a decrease in sucrose preference and an increase in the number of buried marbles. Moreover, CSIS compromised redox homeostasis, targeting enzymes such as GPx, CAT, GST, and caused NF-κB nuclear translocation with a concomitant increase in IL-6 protein expression, without an effect on IL-1β. Flx treatment reversed CSIS-induced depressive- and anxiety-like behaviors, modulated GSH-dependent defense by increasing GLR and GST activity, and suppressed NF-κB activation and cytosolic IL-6 protein expression in socially isolated rats. The present study suggests that changes in the GSH-dependent defense system, NF-κB activation and increased IL-6 protein expression may have a role in social isolation-induced changes in a rat model of depression and anxiety, and contributes to our understanding of the mechanisms that underlie the antidepressant and anti-inflammatory activity of Flx in socially isolated rats.
Gesehen am 07.06.2018